Clinical severity of Omicron subvariants BA.1, BA.2, and BA.5 in a population‐based cohort study in British Columbia, Canada. Issue 1 (29th December 2022) - Russell, Shannon L.; Klaver, Braeden R. A.; Harrigan, Sean P.; Kamelian, Kimia; Tyson, John; Hoang, Linda; Taylor, Marsha; Sander, Beate; Mishra, Sharmistha; Prystajecky, Natalie; Janjua, Naveed Z.; Zlosnik, James E. A.; et al.
Abstract: The SARS‐CoV‐2 variant Omicron emerged in late 2021. In British Columbia (BC), Canada, and globally, three genetically distinct subvariants of Omicron, BA.1, BA.2, and BA.5, emerged and became dominant successively within an 8‐month period. SARS‐CoV‐2 subvariants continue to circulate in the population, acquiring new mutations that have the potential to alter infectivity, immunity, and disease severity. Here, we report a propensity‐matched severity analysis from residents of BC over the course of the Omicron wave, including 39, 237 individuals infected with BA.1, BA.2, or BA.5 based on paired high‐quality sequence data and linked to comprehensive clinical outcomes data between December 23, 2021 and August 31, 2022. Relative to BA.1, BA.2 cases were associated with a 15% and 28% lower risk of hospitalization and intensive care unit (ICU) admission (aHRhospital  = 1.17; 95% confidence interval [CI] = 1.096–1.252; aHRICU  = 1.368; 95% CI = 1.152–1.624), whereas BA.5 infections were associated with an 18% higher risk of hospitalization (aHRhospital  = 1.18; 95% CI = 1.133–1.224) after accounting for age, sex, comorbidities, vaccination status, geography, and social determinants of health. Phylogenetic analysis revealed no specific subclades associated with more severe clinical outcomes for any Omicron subvariant. In summary, BA.1, BA.2, and BA.5 subvariants were associated with differences in clinical severity, emphasizing how variant‐specific monitoring programs remain critical components of patient and population‐level public health responses as the pandemic continues.